EUS Elastography in Evaluating Chronic Liver Disease. Why not from Inside? - Rimbaş, M. (Medical University Publishing House Craiova, 2009)
Fibrosis is the liver’s scarring response to injury, culminating in cirrhosis and its complications. Percutaneous liver biopsy with connective tissue stain is considered more likely a ‘‘silver’’, rather than a ‘‘gold standard’’ for assessing the degree of hepatic fibrosis. That’s why new modalities were recently developed to accurately assess the stage of the liver disease. The term ‘‘elastography’’ describes an imaging technique that conveys information about a tissue’s relative firmness in response to compression, meaning it is more akin to palpation than inspection. Real-time transabdominal elastography represents a new technology for measurement of tissue elasticity integrated in ultrasound systems and can be performed with conventional ultrasound probes during a routine sonography examination. Some of its limitations are that it cannot explore neither all the patients, nor a sufficient size of the liver. In order to overcome these, now that the technology exists, we propose an endoscopic approach from the “inside”.